Selective inhibition of MDR1 P-glycoprotein-mediated transport by the acridone carboxamide derivative GG918 - Wallstab, Antje; Keppler, Dietrich (British journal of cancer, 1999)
The acridone carboxamide derivative GG918 (N-{4-[2-(1,2,3,4-tetrahydro-6,7-dimethoxy-2-isoquinolinyl)-ethyl]-phenyl}-9,10-dihydro-5-methoxy-9-oxo-4-acridine carboxamide) is a potent inhibitor of MDR1 P-glycoprotein-mediated multidrug resistance. Direct measurements of ATP-dependent MDR1 P-glycoprotein-mediated transport in plasma membrane vesicles from human and rat hepatocyte canalicular membranes indicated 50% inhibition at GG918 concentrations between 8 nM and 80 nM using N-pentyl-[3H]quinidinium, [14C]doxorubicin and [3H]daunorubicin as substrates. The inhibition constant Ki for GG918 was 35 nM in rat hepatocyte canalicular membrane vesicles with [3H]daunorubicin as the substrate. Photoaffinity labelling of canalicular and recombinant rat Mdr1b P-glycoprotein by [3H]azidopine was suppressed by 10 μM and 40 μM GG918. The high selectivity of GG918-induced inhibition was demonstrated in canalicular membrane vesicles and by analysis of the hepatobiliary elimination in rats using [3H]daunorubicin, [3H]taurocholate and [3H]cysteinyl leukotrienes as substrates for three distinct ATP-dependent export pumps. Almost complete inhibition of [3H]daunorubicin transport was observed at GG918 concentrations that did not affect the other hepatocyte canalicular export pumps. The high potency and selectivity of GG918 for the inhibition of human MDR1 and rat Mdr1b P-glycoprotein may serve to interfere with this type of multidrug resistance and provides a tool for studies on the function of these ATP-dependent transport proteins.
Gesehen am 23.02.2021